Antibacterial Activity of Melanin from Cuttlefish and Squid Ink - Yuspihana Fitrial; Iin Khusnul Khotimah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Marine environment comprises of many organism which are known to posses bioactive compound as a common means of self-defense or for the protection of eggs and embryos. Class Cephalopods (such as squidand cuttlefish) are notable for their defences, such as jetting escape movements, changes in colouration, toxic venom and inking.This study aims to compare the antibacterial activity of melanin from cuttlefish ink (Sepia sp.) with squid ink (Loligo sp.) against E. coli. Extraction and purification studies were carried out on Sepia and Loligo melanin using a hydrochloric acid 0,5M treatment under mechanical.The melanins were obtained and further evaluated their activity by direct contact methods between melanin and E. coli in nutrient broth.Total microbes was counted by total plate count.Both inks also was tested their activity against E. coli. The results showed that melanin from cuttlefish and squid inks had inhibitory activity at concentrations of 10 mg / ml and 20 mg / mL, respectively reaching 99.99% against E. coli.The inks of both Cephalopods at the same concentration as melanin, did not show any inhibitory activity against E. coli. The melanin of Sepia sp. have a higher antibacterial activity than the melanin of Loligo sp.